The Business Feasibility Study Analysis of a Coffee Shop at the Tempat Biasa Coffee, Jalan Gurilla No. 102 Medan - Siahaan, Leonardo; Muliani, Rizka; Padang, Nova Romadiyah; Lubis, Putri Kemala Dewi (Economic: Journal Economic and Business, 2023)
In the development of the coffee shop business, it has become popular with the public. Tempat Biasa Coffe is a business coffee shop that provides coffee products with different flavors. A coffee shop business can be said to be a viable business if it is stated from a business feasibility study analysis. With business feasibility studies as a science that analyzes the feasibility of a business in terms of legal aspects, marketing market aspects, financial aspects, technical/operational aspects, management and organizational aspects, environmental impact aspects. This research was conducted on the Tempat Biasa Coffee business with the aim of finding out the business feasibility of the Tempat Biasa Coffee business in terms of business feasibility study aspects. This research uses descriptive qualitative research methods with techniques used including interviews, observations and literature studies from articles related to research taken from journals of national reputation and Sinta. From the results of the analysis, the results obtained from the perspective of marketing market aspects, technical/operational aspects, and environmental impact aspects meet the feasibility criteria for a business. Meanwhile, the legal aspects and management and organizational aspects are less feasible. So the ordinary the Tempat Biasa Coffee Shop business still needs to be developed in terms of legal aspects and management and organizational aspects.